Marketing alternatives for Alaska North Slope natural gas : hearing before the Subcommittee on Energy Regulation of the Committee on Energy and Natural Resources, United States Senate, Ninety-eighth Congress, first session on marketing alternatives for Alaska North Slope natural gas, November 16, 1983. - United States. Congress. Senate. Committee on Energy and Natural Resources. Subcommittee on Energy Regulation. (Washington : U.S. G.P.O., 1984)
Includes indexes. Bibliography: p. 89-90. Mode of access: Internet.